Donor‐Appended N, C‐Chelate Organoboron Compounds: Influence of Donor Strength on Photochromic Behaviour. Issue 35 (27th July 2016) - Mellerup, Soren K.; Yuan, Kang; Nguyen, Carmen; Lu, Zheng‐Hong; Wang, Suning
Abstract: Recently, four‐coordinated N, C‐chelate organoboron compounds have been found to show many interesting photochemical transformations depending on the nature of their chelating framework. As such, the effect of substitution on the chelate ligand has been well‐established and understood, but the impact of the aryl groups attached to the boron atom remains less clear. To investigate the effect of enhanced charge‐transfer character, a series of new N, C‐chelate organoboron compounds with donor‐functionalized aryl groups have been synthesized and characterized using NMR, UV/Vis, and electrochemical methods. These compounds were found to possess bright and tunable charge‐transfer luminescence which is dependent on the donor strength of the amino substituent. In addition, some of these compounds undergo photochromic switching, producing dark isomers of various colors. This work establishes that donor‐functionalization of the aryl groups in N, C‐chelate boron compounds is an effective strategy for tuning both the photophysical and photochemical properties of such systems. The new findings also help elucidate the influence of electronic structure on the photoreactivity of N, C‐chelate organoboron compounds which appears to be as important as steric crowding around the boron atom. Abstract : Let there be chelates ! A series of amino‐functionalized N, C‐chelate organoboron compounds have been found to display bright charge‐transfer luminescence and distinct photoreactivity, depending on the donor strength of the amino group and the steric effect of the aryl unit (see figure).